2019
DOI: 10.1155/2019/7530828
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Profile of Wind Diurnal Cycle in the Surface Boundary Layer over the Coast of Cotonou, Benin, under a Convective Atmosphere

Abstract: The characteristics of the wind vertical profile over the coast of Cotonou during wind convective diurnal cycle were explored in this study. Wind data at 10 m above the ground and the radiosonde data in the lower 60 m of the surface boundary layer were used over the period from January 2013 to December 2016. Based on Monin–Obukhov theory, the logarithmic and power laws have allowed characterizing the wind profile. The error estimators of the Root Mean Square Error (RMSE) and the Mean Absolute Error (MAE) were,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 45 publications
3
24
2
Order By: Relevance
“…Despite this limit, these low values enable us to validate these various fitting equations based on the power law model and the logarithmic law as extrapolation models of the wind speed at the Bobo-Dioulasso site. Both laws can therefore be used to model the profile of the vertical wind speed at our study site as reported by the studies in [23] [45]. Near the ground, there is a significant wind speed variation that would be due to the impact of roughness and obstacles encountered on the ground, which decreases with altitude.…”
Section: Vertical Profile Of the Wind Speedmentioning
confidence: 89%
See 4 more Smart Citations
“…Despite this limit, these low values enable us to validate these various fitting equations based on the power law model and the logarithmic law as extrapolation models of the wind speed at the Bobo-Dioulasso site. Both laws can therefore be used to model the profile of the vertical wind speed at our study site as reported by the studies in [23] [45]. Near the ground, there is a significant wind speed variation that would be due to the impact of roughness and obstacles encountered on the ground, which decreases with altitude.…”
Section: Vertical Profile Of the Wind Speedmentioning
confidence: 89%
“…σ is the variance of the air temperature and ( ) 2 σ ω , the variance of the vertical wind component. According to [23], the standard deviation of the vertical wind component ( ) σ ω can be estimated from the parameter ( ) v σ which is the standard deviation of the horizontal wind component:…”
Section: The Log-linear Lawmentioning
confidence: 99%
See 3 more Smart Citations